Terapi Hipnoterapi Untuk Mengurangi Frekuensi Merokok pada Remaja - Fulatul Anifah (Jurnal Keperawatan Muhammadiyah, 2020)
Objective:   The habit of smoking has several negative impacts, for example, causing serious diseases and even death. Groups of people with low economic levels can lead to reduced costs to meet basic needs. One of the interventions that can be done for smokers to reduce their smoking habits is by applying hypnotherapy methods. Hypnotherapy methods are commonly used in social work practice, especially in the arena of clinical social work or medical social work. Hypnotherapy is a therapy that can be used to change human behavior by focusing on a person's subconscious, including reducing a person's desire to smoke by giving suggestions about the adverse effects of smoking to the subconscious. This research aims to describe the hypnotherapy process for adolescents with smoking habits.Methods:   This study used a descriptive qualitative method with five Adolescents in the working area of the Tanah Kali Kedinding Health Center, who underwent hypnotherapy therapy. Data collection techniques using interviews and observation.Results:   The results showed that the hypnotherapy method for clients with smoking habits was divided into seven stages, namely pre-induction, induction, deepening, depth level test, suggestion therapy, hypnotherapeutic technique, and termination. There are differences in the suggestion therapy and hypnotherapeutic technique sections that are tailored to the goals of each adolescent.Conclusion:   Hypnotherapy therapy can reduce the frequency of smoking in Adolescents in the working area of the Takal Health Center.